Project Risk Management Socialization for Employees of the Public Works, Spatial Planning, Housing, and Settlement Areas (PUTRPKP) Department, Takalar Regency - Fitriyanti Mayasari; Misbahuddin .; Azizah Fauziah Misbahuddin (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2026)
Regional infrastructure development is highly complex and therefore vulnerable to various risks that can affect project costs, quality, timelines, and workplace safety. However, the implementation of project risk management in local government agencies still faces various challenges, particularly regarding employees’ understanding of risk identification, risk mitigation strategies, and the preparation of risk registers. Therefore, this Community Service (PkM) activity was conducted in the form of outreach and training on project risk management for employees of the Takalar Regency Public Works, Spatial Planning, Housing, and Settlement Agency (PUTRPKP). The activity aimed to improve employees’ understanding and capacity to systematically apply project risk management in regional infrastructure development projects. The activity materials covered project management concepts, the project risk management process, risk identification, risk response strategies, and the practice of compiling a risk register. The activity was evaluated using a pre-test and post-test method with a 1–4 Likert scale. The evaluation results showed an increase in 13 participants’ understanding across all measurement parameters. Participants’ understanding of the concept of Risk Response Strategy increased from 38% on the pre-test to 85% on the post-test. Meanwhile, participants’ understanding of the Risk Register and how to fill it out increased from 15% to 92%. Additionally, participants were able to practice risk identification and filling out the risk register based on examples of projects frequently undertaken. Consequently, the project risk management awareness-raising activity proceeded successfully and achieved its objectives: enhancing the understanding and practical skills of staff at the Takalar Regency PUTRPKP Department in managing risks associated with infrastructure development projects.